A Four-Gene Prognostic Signature Based on the TEAD4 Differential Expression Predicts Overall Survival and Immune Microenvironment Estimation in Lung Adenocarcinoma - Gong, Xiaoxia; Li, Ning; Sun, Chen; Li, Zhaoshui; Xie, Hao (Frontiers in Pharmacology, 2022)
Background: TEA domain transcription factor 4 (TEAD4) is a member of the transcriptional enhancer factor (TEF) family of transcription factors, that is studied to be linked to the tumorigenesis and progression of various forms of cancers, including lung adenocarcinoma (LUAD). However, the specific function of these genes in the progression of LUAD remains to be explored. Method: Nineteen genes related to the Hippo pathway were analysed to identify the significant genes involved in LUAD progression. The TCGA-LUAD data (n=585) from public databases were mined, and the differentially expressed genes (DEGs) in patients with differential level of TEAD4 were identified. The univariate Cox regression, zero LASSO regression coefficients, and multivariate Cox regression were performed to identify the independent prognostic signatures. The immune microenvironment estimation in the two subgroups, including immune cell infiltration, HLA family genes, and immune checkpoint genes, was assessed. The Gene Set Enrichment Analysis (GSEA) and GO were conducted to analyze the functional enrichment of DEGs between the two risk groups. The potential drugs for the high-risk subtypes were forecasted via the mode of action (moa) module of the connectivity map (CMap) database. Results: TEAD4 was found to be significantly correlated with poor prognosis in LUAD-patients. A total of 102 DEGs in TEAD4-high vs TEAD4-low were identified. Among these DEGs, four genes (CPS1, ANLN, RHOV, and KRT6A) were identified as the independent prognostic signature to conduct the Cox risk model. The immune microenvironment estimation indicated a strong relationship between TEAD4 high expression and immunotherapeutic resistance. The GSEA and GO showed that pathways, including cell cycle regulation, were enriched in the high-risk group, while immune response-related and metabolism biological processes were enriched in the low-risk group. Several small-molecular perturbagens targeting CFTR or PLA2G1B, by the mode of action (moa) modules of Glucocorticoid receptor agonist, Cyclooxygenase inhibitor, and NFkB pathway inhibitor, were predicted to be suited for the high-risk subtypes based on TEAD4 high expression. Conclusion: The current study revealed TEDA4 is an immune regulation-related predictor of prognosis and a novel therapeutic target for LUAD.